Wireless rechargeable sensor networks with separable charger array - Chengjie Xu; Rei-Heng Cheng; Tung-Kuang Wu (International Journal of Distributed Sensor Networks)
Wireless charging technology has been developing rapidly in recent years and has been used to deliver power and provide a new source of energy for wireless rechargeable sensor networks. With current solutions, charging is usually done by a mobile vehicle equipped with a charger, which needs to be waiting on site until the sensor is properly charged. It is possible that some sensors drain their power while the charging vehicle is serving the other. Accordingly, we proposed a solution that uses a single charging vehicle equipped with multiple battery cells, which we call the separable charging array. The battery cell can be unloaded on site with sensor, while the vehicle carries on its mission. A scheduling algorithm, a revised earliest deadline first algorithm, is proposed to work with this new model. In this study, we will demonstrate that the idea of equipping charging vehicle with separable charger array is feasible. In addition, our simulations indicate that the revised earliest deadline first scheduling algorithm does improve the earliest deadline first scheduling algorithm significantly with only minor overhead in scheduling computation time and very few extra chargers. Some modified variations of the proposed revised earliest deadline first algorithm will also be discussed and evaluated.